Design verification for database applications through analysing their support to data lifecycle. (1st January 2011) - Ding, Sun; Tan, Hee Beng Kuan
A large proportion of software systems are database applications. Functionalities provided in these applications are very much associated with their databases. Hence, a lot of designs for these applications can be inferred from their databases. However, most of the design and verification techniques do not take advantage from these important and fundamental characteristics that are generally applied across database applications. Based on these characteristics, this paper proposes a design verification approach for database applications. The proposed verification is grounded on the fact that all data maintained in a database must be inserted, used and removed. These data may also require to be modified. Our evaluation finds that the proposed design verification is useful and effective in detecting essential functionalities that are not provided originally.